Membangun Karakter Kedisiplinan Siswa Mengacu pada Budaya Jepang - Oktaviani Permatasari; Zenita Afifah Fitriyani; Tridjadi Herdajanto; Inuk Wahyuni Istiqomah; Ulfa Rahmawati (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service was carried out at SMAS PGRI 1 Mojokerto City with the main goal of improving student discipline through the application of Japanese-style discipline culture. This activity is designed in a structured manner to have a real and sustainable impact on student behavior and the integrity of educational institutions. The method used is a participatory and applicative approach, so that students not only passively receive information, but also actively engage in the process of learning, reflection, and discipline practice. This approach emphasizes the direct involvement of students in activities that foster awareness, responsibility, and positive habits that support the creation of a conducive learning environment. The results of the implementation of activities are divided into three main categories. First, the short-term results seen immediately after the activity are increased students' motivation and understanding of the importance of discipline. Second, the medium-term results that appear within 1-3 months are in the form of real behavioral changes, such as punctuality, neatness, and compliance with school rules. Third, long-term results that contribute to strengthening the integrity of the institution as a school with a high discipline image. Thus, this community service is expected to be able to become a model for implementing a discipline culture that is effective, sustainable, and relevant to the needs of education in Indonesia.